Peningkatan Peran Pokdarwis Dalam Pengelolaan Desa Wisata Di Desa Pupuan Kecamatan Tegallalang Kabupaten Gianyar - I Nyoman Arto Suprapto; Wayan Pantyasa; Moh. Agus Sutiarso (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
This community service program is located in Pupuan Village, Tegallalang District, Gianyar Regency, with activity partners being Pokdarwis Pupuan Village. The problems faced by partners are the low capacity of human resources in the development and management of tourist villages, the lack of involvement of stakeholders involved in the development of Pupuan Village, the lack of synergy between tourism stakeholders in Pupuan Village, and the absence of tourism village branding for marketing tourism products. The solutions included 1) providing training on tourism village planning and management, 2) Focus Group Discussions and assistance in the framework of establishing synergy between stakeholders, 3) assistance in forming supra-village networks to design tourism village branding. The implementation of training related to planning and governance of tourist villages was enthusiastically attended by Pokdarwis members, village officials, regional heads (Kadus), representatives of traditional villages, and Bumdes staff. Evaluation of the results of the training shows that the training participants have experienced an increase in knowledge with the ability to identify tourist attractions and develop development strategies. The Focus Group Discussion activity also succeeded in agreeing on the branding of a tourist village, namely the Beauty of North Ubud. Coordination with the supra-village network resulted in a village website which was facilitated by the Gianyar Regency Digital Ambassador and the Gianyar Regency Communications and Informatics Service.